Pacific finance sector brief Vanuatu. (Metro Manila, Philippines Asian Development Bank, 2019)
Vanuatu financial system is well served by banks with 11 licensed to operate in the country. The Reserve Bank of Vanuatu serves as the primary monetary authority and regulator of financial institutions. There are 34 insurance companies and intermediaries as well as a pension fund. Yet, the country vulnerability to natural disasters creates financial stability challenges and requires a more responsive and appropriate monetary policy. Financial inclusion is relatively high in Vanuatu, although access for outer island residents needs to be improved as too does credit availability for small and medium-sized business
Keywords: Finance -- Vanuatu; Industrial policy; Electronic books